Reducing cognitive vulnerability to depression: a preliminary investigation of MEmory Specificity Training (MEST) in inpatients with depressive symptomatology. - Raes, F; Williams, J; Hermans, D (2009)
Reduced specificity of autobiographical memory retrieval represents an enduring vulnerability factor for depression. The present study is a preliminary evaluation of a newly developed group-based intervention program to increase specificity of memory retrieval. The MEmory Specificity Training (MEST) was administered on a weekly basis for 4 consecutive weeks to 10 inpatients with depressive symptomatology. Whereas earlier studies found that memory specificity does not improve following treatment as usual, the present results showed that participants' retrieval style became significantly more specific following MEST. These results suggest that the MEST may offer a potential and promising intervention to tackle a core cognitive process involved in depression and depressive vulnerability.